Gear-Shaper Cutter with Curvilinear Side Flank Face - Siecla, Roman; Legutko, Stanislaw (Manufacturing Technology Journal, 2012)
The paper presents a concept of the design of gear shaper cutters with curvilinear side flank faces. The problem of forming the outline of the cutting edge of the gear shaper wedge has been discussed and the possibilities of execution of this type of knives have been indicated. The method of forming the rake face of curvilinear side flank face has been presented.
Keywords: gear wheels; curvilinear flank face; gear shaper cutter design